Singkat: A Keyword-Based URL Shortener and Click Tracker Package for Django Web Application - Prasetyadi, Gottfried; Tri, Utomo; Benny, Achmad (International journal of advanced computer science & applications, 2018)
In recent years, Python has been gaining popularity as web scripting/programming language. In this research we propose Singkat, an open source uniform resource locator (URL) shortener package with web user interface built using Python-based Django web framework. It can be deployed and customized in any web project based on Django framework. This makes sure that administrators can gain control over data in their own environment. Users can create shortened links using base62 values to generate pseudo random keyword. To minimize phishing and other abuses, only registered users can create shortened link using their chosen keyword, and it is possible to preview a link before accessing it. Registered users can also monitor each click and get useful information. We also ran some tests to measure Singkat’s performance and functionality.